Bridging the Digital Divide in Archipelagic Marine Tourism: A Study of Telecommunications Infrastructure and Traffic Engineering in Raja Ampat, Indonesia - Muhammad Riza Darmawan; Widya Cahyadi; Martiana Kholila Fadhil; Dananjaya Endi Pratama; Vina Dewi Ramadhanty; Candra Putri Rizkiyah Ramadhani (International Journal of Electrical and Intelligent Engineering, 2026)
This study assesses telecommunications infrastructure and traffic engineering in Raja Ampat, Indonesia, comprising four main islands and over 1,500 smaller islands across 46,000 km² of marine protected area. Field measurements at 48 points over 2023–2024, combined with QoS evaluation and SWOT-based assessment, revealed adequate signal coverage (–65 to –80 dBm) only within 1 km of shore-based stations, degrading to –95 to –110 dBm at offshore diving locations (5–15 km), where throughput dropped to 2–5 Mbps against the 10–50 Mbps requirement. A Modified Erlang B Model showed 3–4× seasonal traffic variation, with peak busy-hour demand reaching 2.5–4 Gbps from 300–560 concurrent users and the Misool–Salawati backhaul reaching 95% utilization. Capacity forecasting (R² = 0.91) indicates saturation within 2–3 years. An integrated approach combining additional base stations, expanded backhaul, LEO satellite integration, and renewable energy is essential.